Modelling of hydrogen atoms reflection from an annealed tungsten fuzzy surfaces. (March 2021) - Liu, D.H.; Dai, S.Y.; Wada, M.; Yang, K.R.; Chen, J.Y.; Liu, D.P.; Cherenda, N.; Wang, D.Z.
Highlights: Reflection property of hydrogen atoms have been investigated by SURO-FUZZ. Annealing effect of the tungsten fuzz is studied. Hydrogen reflection coefficient is in reasonable agreement with measurements. Abstract: Modelling of the hydrogen reflection on tungsten smooth and fuzz surfaces under the low-energy hydrogen plasma bombardment has been performed with the three-dimensional kinetic Monte Carlo code SURO-FUZZ. The relative reflection coefficient of hydrogen atoms, i.e. the ratio of reflected hydrogen atoms on the tungsten fuzz surface to that on the tungsten smooth one, is employed to illustrate the change in the hydrogen reflection on the tungsten fuzz and smooth surfaces. The simulated relative reflection coefficient of hydrogen atoms shows a large discrepancy with the measured values obtained in the hydrogen plasma bombardment experiment. The impinging hydrogen particles with a low incident energy result in a small sputtering and large residual nanostructure existing on the tungsten fuzz surface, which lead to a small change in the relative reflection coefficient of hydrogen atoms. The discrepancy between simulations and experiments motivates us to take the impacts of the annealing effect into account in SURO-FUZZ code. Implementation of annealing effect into SURO-FUZZ has been benchmarked against the experimental data. The simulated temporal evolution of the hydrogen reflection coefficient is in reasonable agreement with the experimental data.